2016
DOI: 10.1111/asj.12726
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on accuracy of different nonlinear models in predicting growth of Podolica bulls

Abstract: Animal growth does not follow a linear pattern, being explained mathematically by functions that have parameters with biological meaning. These parameters are used to estimate the expected weight of animals at specific ages. Several nonlinear models have been used to describe growth. This study was carried out to estimate the parameters of logistic, Gompertz, Richards and von Bertalanffy growth curve models in a sample of Podolica young bulls to determine the goodness of fit. Animals were weighed every 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
(32 reference statements)
0
13
1
3
Order By: Relevance
“…According to the studied growth functions, Gompertz reached the highest numerical estimated value for the asymptotic weight (A) and the Logistic function had the lowest value. Although the Gompertz model had the highest asymptotic weight value, the Richards model was the best to fit the data depending on the goodness of fit criteria and asimilar trend was found by Selvaggi et al, (2017). The estimated maturity rate parameter (K) by the Gompertz model was similar to that obtained by the Richards model; both values were lower than those attained through the Logistic model (0.008).…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…According to the studied growth functions, Gompertz reached the highest numerical estimated value for the asymptotic weight (A) and the Logistic function had the lowest value. Although the Gompertz model had the highest asymptotic weight value, the Richards model was the best to fit the data depending on the goodness of fit criteria and asimilar trend was found by Selvaggi et al, (2017). The estimated maturity rate parameter (K) by the Gompertz model was similar to that obtained by the Richards model; both values were lower than those attained through the Logistic model (0.008).…”
Section: Resultsmentioning
confidence: 70%
“…Several studies reported that Richards model was the best for describing growth pattern in cattle (Tjørve and Tjørve, 2010;Velásquez et al, 2013;Goldberg and Ravagnolo, 2015;Gano et al, 2016 andTutkun, 2019). The logistic function was found to be the least accurate based on AIC and BIC (Forni et al, 2009, Gano et al, 2016and Selvaggi et al, 2017. The estimates of AIC and BIC showed wide range reported by many authors (42.05 to 201857 and 41.43 to 201889, respectively) for the Gompertz model (Velásquezet al,2013, Goldberg and Ravagnolo, 2015and Gano et al, 2016 ranging from 183379 to 189150 and 183560 to 189189, respectively for Richard model and ranging from 184623 to 206277 and 184749 to 206309, respectively for Logistic model (Goldberg andRavagnolo, 2015 andGano et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Malhado, et al [43] showed that both Gompertz and Logistic models provided the best fit of the growth curve in sheep. In addition, the logistic and Gompertz showed the best fit for the growth of young bulls with fewer iterations needed to achieve convergence [44].…”
Section: Body Weight Carcass Weight and Dressing Percentagementioning
confidence: 98%